Computer Simulation of Fluid Flow Through a Venturi Nozzle of Different Configurations - Avdieieva, L.; Makarenko, A.; Dekusha, H. (Science and Innovation, 2022)
Introduction. Hydrodynamic cavitation, as an effective way of local energy concentration to create powerful dynamic effects, has been widely used to intensify many energy-intensive operations related to processing comp lex heterogeneous dispersed systems. Problem Statement. The high cost of equipment for physical experiments and the difficulties related to reproducing complex hydrodynamic processes in laboratory conditions make it necessary to use modeling/simulation methods. Recently, mathematical and computer modeling has become one of the most effective information technologies that determine the rapid development of advanced fields of science and technology. Purpose. The purpose of this research is to predict the behavior of fluid motion inside the Venturi nozzles of different configurations in the case of changing thermal process parameters, with the use of ANSYS Fluent computational package. Materials and Methods. The Simple algorithm of the Patankar method, which involves a second-order accuracy counter flow scheme for convective terms in the momentum conservation equation, for the kinetic turbulent energy equation and the turbulent energy dissipation equation, has been used. The “Realizable” modified k-ε model of turbulence and Euler’s model (multiphase model) have been applied. The standard ANSYS ICEM CFD package has been employed to generate the calculation grid. Results. The model chosenfor computer simulation has proven its effectiveness and allowed us to establish some patterns of fluid motion along the axis of the Venturi nozzle. Based on the simulation results, the dependences of changes in the pressure in the case of varying neck diameter and opening angle of the Venturi nozzle diffuser have been constructed. It has been shown that the highest intensity of cavitation is reported in the experimental nozzle with opening angle of the diffuser αdif = 12° for all diameters of the nozzle neck. Conclusions. The use of highly specialized software and modeling systems allows us to better understand the behavior of the flow in closed channels of different configurations. Computer simulation of fluid motion in Venturi nozzles has enabled predicting the processes of occurrence and development of hydrodynamic cavitation in different sections of the nozzle.